“Territory of no politics”: The Role of Entertainment Content in the Political Socialization of Russian Youth by the Example of Steam and YouTube - Dmitry A. Kazantsev; Dmitry A. Kachusov (RUDN Journal of Political Science, 2025)
The aim of the study is to examine the impact of entertainment content on the political socialization of the Russian youth. The empirical basis of the study includes data from a mass survey of young people in four regions of Russia (Altai Krai, Tomsk Region, Novosibirsk Region, and the Republic of Altai) with a sample size of 1,257 respondents, as well as the results of a neural network analysis and content analysis of user comments on Steam and YouTube. The survey findings reveal a small «core» of young users (up to 10 %) who recognize the political subtext of entertainment content, while the majority (up to 80 %) prefer to avoid politics, deny its influence on their values and attitudes, and perceive games and videos exclusively as leisure activities. Neural network analysis identified the key thematic clusters (mega-variables) in user discussions: themes of war and peace, virtuality and reality, patriotism and protest, social justice, and distrust of authorities. Differences in discourse were established: on the gaming platform, political discussions tend to be more abstract and philosophical, whereas on the video-hosting platform, the discourse is significantly more politicized, dominated by assessments of current political agendas and polarization between «ultra-patriots» and the opposition. The study concludes that entertainment content plays an ambivalent role as a distinct channel of political socialization, subtly transmitting political narratives that are consciously perceived by an active minority of young people while potentially exerting an indirect influence on the passive majority. The findings highlight the segmentation of the youth audience and the need to consider this specific feature when analyzing the impact of digital environments on the formation of political identity.